Religious tourism and the factors and opportunities that motivate tourists to pursue religious tourism-Iraq as a sample - Ahmed Obaid Oraibi (Peerian Journals Publishing, 2024)
Religious tourism is considered one of the most important industries in science, and it is considered to have a significant impact on the world in economic terms. Therefore, the concepts of religious tourism and how they have developed over time were discussed here, as well as the effects of the Covid-19 pandemic on religious tourism, as well as the opportunities provided by religious tourism from Where the development of the economies of countries that are considered religious tourism destinations and the factors that affect the tourist in religious tourism, as well as the factors that motivate the tourist to religious tourism, and Iraq was taken as a sample because it is considered one of the countries with great religious tourist attraction, and a statistical study was conducted on The number of tourists who flock to the city of Karbala because it is considered one of the important tourist cities in Iraq, where the results concluded that the number of Muslim tourists in particular is a large number and has a clear economic impact, especially its impact on the development of the Iraqi economy because it is the sample that was addressed here where it can and from Through the stimuli and factors discussed here, the increase in this number of tourists in a way that positively affects the Iraqi economy in particular and the global economy in general.
Keywords: Religious tourism; tourism activity; Iraq